Linguistic Factors Responsible for the Occurrence of the Varieties in Anaang Language and The Standardization of The Language - Aniekan NYARKS, Ph.D (Genius Journals, 2022)
Having realized that there are four varieties of the Anaang Language via Anaang Central Dialect (ACD), Anaang Northern Dialect (AND), Anaang Southern Dialect (ASC), and Anaang Western Dialect (AWD); this study aims at discovering the linguistic factors responsible for the occurrence of the varieties. With this objective in mind, we used survey and library sources; stratified random sampling with 80 Anaang indigenes using 20 Anaang wordlist and five simple sentences for interpretation. Later, a comparative analysis was employed. It was realized that interference and bilingualism are responsible for the varieties in the language. Furthermore, it is suggested that the methods such as modernization, borrowing, adaptation, adoptation, codification and literary production should be employed in other to achieve standardization in the language
Keywords: Linguistic Factors; Varieties; Standardization and Anaang Language